Effects of dietary chromium and ascorbic acid supplementation on digestion of nutrients, serum antioxidant status, and mineral concentrations in laying hens reared at a low ambient temperature - Şahin, Kazım; Şahin, Nurhan; Küçük, Ömer (Springernature, 2002)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate, CrPic) and vitamin C (L-ascorbic acid) supplementation on the digestion of nutrients and serum concentration of some antioxidant vitamins and minerals of laying hens (Hy-Line) reared at a low ambient temperature (6.8degreesC). One hundred twenty laying hens (32 wk old) were divided into 4 groups, 30 hens per group. The laying hens were fed either a basal diet or the basal diet supplemented with either 400 mug of Cr/kg diet, 250 Mg of L-ascorbic acid/kg diet, or 400 mug of Cr plus 250 mg L-ascorbic acid/kg diet. The digestibility of nutrients (DM, OM, CP, and EE) increased by the supplementation of chromium and vitamin C (p < 0.05). Supplemental chromium and vitamin C also increased serum vitamin C and E but decreased malondialdehyde concentrations (p < 0.05). Additionally, supplemental chromium and vitamin C caused an increase in the serum concentrations of Fe, Zn, Mn, and Cr (p < 0.05) but a decrease in Cu concentration. The results of the present study showed that each dietary supplement influenced most of the parameters measured in a similar way. Also, a combination of the two supplements resulted in an additive effect, and supplementing a combination of vitamin C (250 mg/kg of diet) and chromium (400 mu g Cr/kg diet) may offer a potential protective management practice in preventing cold-stress-related depression in the performance of laying hens.
Keywords: cold stress; chromium; vitamin C; MDA; minerals; laying hen